100 ideas that changed architecture. - Weston, Richard, 1953- (London : Laurence King Publishing, 2011)
This inspiring book chronicles the most influential ideas that have shaped architecture. Entertainingly written by an expert on architecture, it provides a concise history of the subject, and offers a fascinating resource to dip into for the general reader. Starting with the basic building 'components' of door, window, column and beam and the Classical orders, it then goes on to explore historical movements such as the Picturesque and Beaux-Arts, innovative materials such as steel and reinforced concrete, technical innovations, such as the lift and electric lighting, through to modern movements such as Universal Design and Deconstruction. Arranged in a broadly chronological order, the ideas are presented through fascinating text and arresting visuals, 100 Ideas that Changed Architecture explores when each idea first evolved and the subsequent impact it has had up to the present day.
Keywords: Architectuur; Architectuurgeschiedenis; Bouwkunst